2012
DOI: 10.1021/ac301243k
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Predictive Model of Alzheimer’s Disease Progression Using Capillary Electrophoresis–Mass Spectrometry Metabolomics

Abstract: Alzheimer's disease (AD) is the most prevalent form of dementia with an estimated worldwide prevalence of over 30 million people, and its incidence is expected to increase dramatically with an increasing elderly population. Up until now, cerebrospinal fluid (CSF) has been the preferred sample to investigate central nervous system (CNS) disorders since its composition is directly related to metabolite production in the brain. In this work, a nontargeted metabolomic approach based on capillary electrophoresis-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
90
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 33 publications
10
90
0
2
Order By: Relevance
“…Lysine, is a strictly ketogenic amino acid that is required for the synthesis of L-carnitine. L-Carnitine is the sole transporter of fatty acids to mitochondria for energy production and carnitine level has been shown to be lower in CSF of MIC-AD and AD patients than in CSF from non-AD subjects [98].…”
Section: Neuropsychiatric Diseasesmentioning
confidence: 99%
“…Lysine, is a strictly ketogenic amino acid that is required for the synthesis of L-carnitine. L-Carnitine is the sole transporter of fatty acids to mitochondria for energy production and carnitine level has been shown to be lower in CSF of MIC-AD and AD patients than in CSF from non-AD subjects [98].…”
Section: Neuropsychiatric Diseasesmentioning
confidence: 99%
“…While CE-MS is very effective for hydrophilic metabolites, it is also possible to perform the electrophoresis using capillaries packed with a reverse-phase packing. [91] Direct use of cerebrospinal fluid [92] and serum [93] in CE-MS led to protein precipitation within the capillary. It was necessary to use ultrafiltration of these fluids to avoid this issue.…”
Section: Modern Metabolomicsmentioning
confidence: 99%
“…Also, MSEA (Tab. 3) highlighted that two independent studies indicated alterations in methionine metabolism (Czech et al 2012;Ibanez et al 2012).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%